Textile electrodes for heart rate measurement: A comparative study for firefighters' monitoring - Ferreira, André Filipe Gonçalves (2019)
This work compares the performance of wet gel electrodes and textile-based electrodes for monitoring the firefighters' heart rate during on-duty missions. Both types of electrodes are connected to a customized wearable node that acquires the bio-signals and computes the heart rate. Both types of electrodes were evaluated by two subjects and in three different scenarios: sitting, standing and moving the arms, and walking. The tests have demonstrated that in static scenarios the results obtained for both type of electrodes are comparable. However, in dynamic scenarios, the performance of textile electrodes worsens, especially when the wearer is moving the arms. Although the results obtained from textile electrodes during walking are not as good as the wet get electrodes, its information is still useful for monitoring the firefighters' heart rate.